Oligosaccharides in 4 different milk groups, Bifidobacteria, and Ruminococcus obeum - Coppa, Giovanni V; Gabrielli, Orazio; Zampini, Lucia; Galeazzi, Tiziana; Ficcadenti, Anna; Padella, Lucia; Santoro, Lucia; Soldi, Sara; Carlucci, Antonio; Bertino, Enrico; Morelli, Lorenzo (Journal of pediatric gastroenterology and nutrition, 2011)
The aim of this study was to identify a link between the total amount of breast milk oligosaccharides and faecal microbiota composition of newborns at the end of the first month of life, with special attention paid to bifidobacteria, and establish the role, if any, of the different oligosaccharides in determining the gut microbiota composition. Milk oligosaccharide groups were identified by high-performance anion exchange chromatography analysis. DPCRNA from newborns' faecal samples at 30 days of life was isolated and processed by polymerase chain reaction analyses that allow the identification of 6 species of bifidobacteria (adolescentis, bifidum, breve, catenulatum, longum, infantis) and Ruminococcus spp; denaturing gradient gel electrophoresis analysis was also performed. No substantial differences in bifidobacteria species composition within milk groups 1, 2, and 3 were observed; however, infants fed with group 4 milk show a microbiota characterised by a greater frequency of Bifidobacteria adolescentis and the absence of Bifidobacteria catenulatum. For the first time, a high percentage of the Ruminococcus genus in infants fed with all milk groups was found. Our data show that milk groups 1, 2, and 3, containing an amount of oligosaccharides ranging within 10 to 15 g/L, share a substantially identical composition of the intestinal microbiota in breast-fed infants, despite quali-quantitative difference in oligosaccharides content. Newborns taking milk with only 5 g/L of oligosaccharides (group 4) harbour a different intestinal microbiota.